2019
DOI: 10.4081/nhs.2019.394
|View full text |Cite
|
Sign up to set email alerts
|

Decapod assemblage from the late Miocene (early-middle Messinian) of the Romagna Apennines nearby Brisighella, Emilia-Romagna (N Italy)

Abstract: An assemblage of axiidean and brachyuran decapods is reported from the late Miocene pre-evaporitic (early-middle Messinian) limestone of Cò di Sasso, nearby Brisighella (Ravenna, Emilia- Romagna), located in Romagna Apennines (NE Italy). Except Monodaeus bortolottii Delle Cave, 1988 (Xanthidae MacLeay, 1838), which is reported here for the first time in Miocene, all the other specimens have been assigned to species previously known in the Italian Miocene (Messinian s.l.), but never reported in this area. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…No crustacean records were previously reported from these layers, except for a single decapod caridean assigned to Palaemon monsdamarum PaSini & garaSSino, 2018, from the Messinian tripoli of Mondaino (Rimini, Emilia-Romagna) (PaSini & garaSSino 2018). Other previous reports of Miocene decapods from the Romagna Apennines are limited to some anomurans, axiideans, and brachyurans from two localities nearby Brisighella (Ravenna, Emilia-Romagna), which belong to the early-middle Messinian (PaSini et al 2019). Hence, the new report from Valmarecchia outcrops enhances the scarce knowledge on the presence and distribution of crustaceans around the palaeo-Adriatic Gulf during the middle-late Miocene prior to the onset of the Mediterranean Salinity Crisis.…”
Section: Introductionmentioning
confidence: 59%
“…No crustacean records were previously reported from these layers, except for a single decapod caridean assigned to Palaemon monsdamarum PaSini & garaSSino, 2018, from the Messinian tripoli of Mondaino (Rimini, Emilia-Romagna) (PaSini & garaSSino 2018). Other previous reports of Miocene decapods from the Romagna Apennines are limited to some anomurans, axiideans, and brachyurans from two localities nearby Brisighella (Ravenna, Emilia-Romagna), which belong to the early-middle Messinian (PaSini et al 2019). Hence, the new report from Valmarecchia outcrops enhances the scarce knowledge on the presence and distribution of crustaceans around the palaeo-Adriatic Gulf during the middle-late Miocene prior to the onset of the Mediterranean Salinity Crisis.…”
Section: Introductionmentioning
confidence: 59%
“…Recently, this species was also reported from the Early Pleistocene of Poggi Gialli (Sinalunga, Tuscany) byDe Angeli, Garassino & Pasini in Baldanza et al (2017) and from the Pliocene of Faenza (Ravenna, Emilia-Romagna)(Pasini et al 2018). Finally,Pasini et al (2019) reported M. bortolottii specimen from the Miocene of Brisighella (Ravenna, Emilia-Romagna).The report of M. bortolotii from Basilicata attests to its wide palaeogeographic distribution in Italy and its wide stratigraphic range from the Miocene to the Early Pleistocene.…”
mentioning
confidence: 75%
“…Goneplax gulderi was previously reported from the Miocene of Austria (Baden) (Bachmayer, 1953) and Miocene and Pliocene of Italy (Tuscany, Emilia-Romagna) (Pasini et al 2019, 2020). Its first report in North Africa enlarges its palaeobiogeographic range around the Proto-Mediterranean Basin.…”
Section: Systematic Paleontologymentioning
confidence: 88%